Early Posterior Corneal Changes and Belin/Ambrósio Scores Following Photorefractive Keratectomy: A Pentacam Study - Konuralp Yakar; Göksu Alaçamlı; Gökhan Özgür (Ophthalmology and Therapy)
Abstract Introduction To evaluate early postoperative changes in the posterior corneal surface, anterior chamber parameters, and Belin/Ambrósio Enhanced Ectasia Display (BAD) scores following photorefractive keratectomy (PRK) using Pentacam tomography. Methods This observational study included 102 eyes of 51 patients (mean age 28.43 ± 6.27 years) undergoing alcohol-assisted PRK for myopia and/or astigmatism. Preoperative and 1-month postoperative assessments were performed using the Pentacam system, measuring, anterior chamber depth (ACD), anterior chamber volume (ACV), central corneal thickness, posterior keratometry, posterior elevation, and BAD scores. PRK was conducted with a WaveLight® EX 500 excimer laser, followed by mitomycin-C application. Statistical analysis utilized paired t-tests and Pearson’s correlation. Results At 1 month post-PRK, ACV significantly decreased (p < 0.01), while ACD reduction was not significant (p = 0.40). Posterior keratometry (K1, K2, Kmean) and astigmatism decreased (p < 0.01), with a mean posterior elevation increase of −2.50 ± 2.94 µm (p < 0.01). A weak negative correlation was observed between maximum posterior elevation difference and ablation depth (p = 0.03, r = −0.20) and ablation depth/preoperative pachymetry ratio (p = 0.03, r = −0.20). BAD-D scores (Dp, Dt, Da, total D) significantly increased (p < 0.01), except for Df (p = 0.41). No correlation was found with preoperative pachymetry or residual stroma. Conclusions PRK induces minimal posterior corneal protrusion and BAD score changes at 1 month, potentially mimicking early ectasia. Multimodal testing is advised for accurate ectasia detection. Larger, longer-term studies are needed to validate these findings.